Isolation and characterization of the tissue and development-specific potato snakin-1 promoter inducible by temperature and wounding - Almasia, Natalia Ines; Nahirñak, Vanesa; Hopp, Horacio Esteban; Vazquez Rovere, Cecilia (Pontificia Universidad Catolica de Valparaiso, 2021)
Snakin-1 (StSN1) is a broad-spectrum antimicrobial peptide isolated from Solanum tuberosum. Homologous proteins have been identified in a wide range of species but there is no apparent consensus in the roles they play. A 1394 bp fragment of the 5’upstream region of StSN1 gene, designated PStSN1, was isolated from the potato genome and sequenced. Bioinformatics analyses revealed a total of 55 potential regulatory motifs related to tissue-specificity, stress, defence and hormone responsiveness, among others. PStSN1 spatial and temporal activity was studied in transgenic Arabidopsis plants expressing a reporter gene under this promoter control (PStSN1::GUS). Histochemical staining revealed PStSN1::GUS expression in the root vasculature, cotyledons, young leaves and floral organs. Moreover, GUS staining was detected in young developmental stages gradually decreasing as the plant aged. Stress treatments on transgenic plants showed that PStSN1 activity was induced by high/low temperature and wounding. The characterization of PStSN1 in a model plant establishes a framework for the understanding of its possible biological functions and provides a potential tool for plant modification through genetic engineering.